POTENSI PRODUKSI MINYAK ATSIRI DARI LIMBAH KULIT KAYU MANIS PASCA PANEN - Susanti, Neni; Gandidi, Indra Mamad; Susila ES, M.Dyan (FT UNILA, 2013)
Kayu manis (Cinnamomum burmanii BL) is known and cultivated for its aromatic content. In the previous experiment the powder of kayu manis leather can be extracted to be atsiri oil. And the rubbish like; leaf, scrap, the powder from cutting tree, trank are the parts of wood leather that haven’t been used yet, so it will be appear as a problem for the environment. If the rubbish are extacted by steam and water destilation it will produce atsiri oil with good quality and good cost, as a mix ingredient of medicine beverages, food, and parfume. The experiment goal is to filter by using arrange destilation tool to get output the process is an optimal rendeman atsiri oil. An the extract metode used is steam and water destilation. To get a good filter output should be treated by parameter variety suitable with test tool performance they are; pressure variety (1 atm; 1,65 atm; 1.85 atm), temperatur (99oC; 114oC; 119oC) and resident time (1 hour; 2 hour; 3hour). The result of the testing is an output of the most atsiri oil, it is at pressure 1,85atm, the ingredient weigh is 750 gram, and the resident time 3 hour. Where, the maximum percentage rendeman from the leaf, powder, and scrap until 1,63 %; 1,49%; and 1,42%. Atsiri oil has not reached optimum point, because the pressure has not been optimal and the capacity of the tank is limited. The percentage rendeman up to 1% can give chance for the rubbish of kayu manis to be processed become atsiri oil. So that, this research can be continue by project for study of home industry.Keywords : Destilation process, atsiri oil, kayu manis, the rubbish of kayu manis leather.